ADAPTIVE INDOOR POSITIONING MODEL BASED ON WLAN FINGERPRINTING FOR MULTI-FLOOR ENVIROMENTS - Al-Shami, Iyad H.M., 1977-, author; Noor Azurati Ahmad @ Salleh, Dr., supervisor; Shamsul Sahibuddin, Prof.Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2016